Disparities in the levels of educational development: a geographic analysis of Kashmir Valley - Shahnaz Mohiuddin,; Haseena Hashia, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
The problem of regional disparities in the levels of social and economic development is a universal phenomenon. Educational attainments of the population in a region determine its standard of living and overall socio-economic development. India with considerable inequalities in education sector is committed to reduce these inequalities under various programmes. In Kashmir Valley there are considerable inequalities among tehsils (areas) with respect to literacy level, opportunities for primary, secondary and higher education, facilities for professional courses and training in specialized technical skills. These inequalities are bound to create various socio-economic and political problems. Therefore, it is essential to ensure even development of educational facilities in both economically developed and backward tehsils. The indicators to be used in the present study have been assigned statistical weights derived through factor analysis method. The indicators have been standardized and on the basis of factor matrix, an index of overall development has been prepared. All tehsils have been ranked according to their index values and classified into highly developed, developed, backward and highly backward tehsils according to their quartile values. The changes in the index values have been examined to trace the direction of development.